TRENDS AND CONSEQUENCES OF INTRODUCTION OF AUTOMATION AND DIGITALIZATION OF ENTERPRISES, INDUSTRY, AND ECONOMY - Sergeevna Sivash, Olga; Dmitrievna Burkaltseva, Diana; Vladimirovna Kurianova, Irina; Valerievich Nekhaychuk, Dmitry; Alekseevich Stepanov, Alexey; Sergeevich Tyulin, Andrey; Niyazbekova, Shakizada (Revista Inclusiones, 2020)
The authors consider the problems, trends and consequences of automation of processes in various sectors of the economy, including industry. These activities are becoming more and more relevant in the current era of digitalization and the formation of the digital economy both abroad and in Russia. Currently in the process of automation, which includes robotics and automation of technological processes (production machines); development in the field of artificial intelligence; open systems (Blockchain); big data concept; software algorithms and systems (software); neural networks – it is not possible to adequately assess the consequences and possibilities of qualitative changes in the activities of enterprises in its implementation. The purpose of this research is to study the trends and consequences of the automation introduction and of the implementation of enterprise, industry and economy digitalization processes. Accordingly, the objectives of the research are: to identify the main directions and problems of the introduction of automation, to study the current state of the labor market in the world, to consider the Blockchain technology and its advantages in various fields.